Pentingnya Pendidikan Disiplin dalam Membentuk Karakter Orang Muda - Memah Grifol Jeyral; Juwinner Dedy Kasingku; Winda Novita Warouw (Journal on Education, 2023)
Young people are the successors of the church and nation and will be the future inheritors of its mission, embodying the church and nation’s hopeful future. However, many tendencies among young individuals often deviate from fundamental principles. Hence, it is crucial for young people to uphold moral principles and counteract immoral traits and behaviors. By doing so, young Christians can faithfully abide by every commandment of God. In this study, the author utilizes a qualitative research approach, specifically a literature review, to explore the significance of discipline in Christian education, drawing insights from the life of Samson, a prominent figure in the Bible. Young people must embrace discipline as they uphold principles and regulations, while also fostering a closer relationship with God. Furthermore, parents bear a significant responsibility in shaping the character of young individuals.